Increasing persistency in lay and stabilising egg quality in longer laying cycles. What are the challenges?. Issue 3 (3rd May 2016) - Bain, M. M.; Nys, Y.; Dunn, I.C.
Abstract: In the past 50 years, selection starting initially at the breed level and then using quantitative genetics coupled with a sophisticated breeding pyramid, has resulted in a very productive hybrid for a variety of traits associated with egg production. One major trait currently being developed further is persistency of lay and the concept of the "long life" layer. Persistency in lay however cannot be achieved without due consideration of how to sustain egg quality and the health and welfare of the birds in longer laying cycles. These multiple goals require knowledge and consideration of the bird's physiology, nutritional requirements, which vary depending on age and management system, reproductive status and choice of the selection criteria applied. The recent advent of molecular genetics offers considerable hope that these multiple elements can be balanced for the good of all in the industry including the hens. The "long life" layer, which will be capable of producing 500 eggs in a laying cycle of 100 weeks, is therefore on the horizon, bringing with it the benefits of a more efficient utilisation of diminishing resources, including land, water, raw materials for feed as well as a reduction in waste, and an overall reduced carbon footprint.